MENINGKATKAN KUALITAS PADA PROSES PENGISIAN PULSA ELEKTRIK DENGAN MENGGUNAKAN METODE SIX SIGMA - Johnny Harjono; Jeddy J. Sardjono (Journal of Business Strategy and Execution, 2010)
In globalization era recently, communication became a very important needed, not only a few industries engaged in telecommunications to compete getting a lot of customers, it is also done by the distribution industry of electrical pulses, one of them is GrahaPulsa.com. GrahaPulsa.com should notice to customer satisfaction in the process of charging the pulse. Recently GrahaPulsa.com has problems which is the slowness off reload transaction processing, thereby affected customer satisfaction. This significantly effect in the sales process pulses. Therefore, is used a concept called "Six Sigma" that seeks to reduce the potentially become a problem and also to improve the quality of the pulse charging process to make it better. The measures contained in the Six Sigma Define - Measure - Analyze - Improve - Control (DMAIC). The solution is obtained by making the process of perfecting the technology and procedures within the company that are directly related to the electrical pulse charging and control process, so the process improvements that have been made can be maintained and to prevent the defect does not happen again and to improve the quality of the process of charging electric pulse. Six Sigma is proven to improve the quality of charging electrical pulses by increasing the speed of the charging the pulse at GrahaPulsa.com.